The physiologic responses to a fluid bolus administration in old and young healthy adults - Cunningham, Cordell; Tapking, Christian; Salter, Michael; Seeton, Roger; Kramer, George C.; Prough, Donald S.; Sheffield-Moore, Melinda; Kinsky, Michael P. (Perioperative medicine, 2022)
Background Organ function is known to decline with age. Optimizing cardiac, pulmonary and renal function in older adults has led to significant improvements in perioperative care. However, when substantial blood loss and fluid shifts occur, perioperative outcomes still remains poor, especially in older adults. We suspect that this could be due to age-related changes in endothelial function-an organ controlling the transport of fluid and solutes. The capillary filtration coefficient (CFC) is an important determinant of fluid transport. The CFC can be measured in vivo, which provides a tool to estimate endothelial barrier function. We have previously shown that the CFC increases when giving a fluid bolus resulting in increased vascular and extravascular volume expansion, in young adults. This study aimed to compare the physiologic determinants of fluid distribution in young versus older adults so that clinicians can best optimize perioperative fluid therapy. Methods Ten healthy young volunteers (ages 21-35) and nine healthy older volunteers (ages 60-75) received a 10 mL/kg fluid bolus over the course of twenty minutes. Hemodynamics, systolic and diastolic heart function, fluid volumetrics and microcirculatory determinants were measured before, during, and after the fluid bolus. Results Diastolic function was reduced in older versus younger adults before and after fluid bolus (P < 0.01). Basal CFC and plasma oncotic pressure were lower in the older versus younger adults. Further, CFC did not increase in older adults following the fluid bolus, whereas it did in younger adults (p < 0.05). Cumulative urinary output, while lower in older adults, was not significantly different (p = 0.059). Mean arterial pressure and systemic vascular resistance were elevated in the older versus younger adults (p < 0.05). Conclusion Older adults show a less reactive CFC to a fluid bolus, which could reduce blood to tissue transport of fluid. Diastolic dysfunction likely contributes to fluid maldistribution in older adults.